Education Reform, Equal Opportunity and Educational Achievement: Do Trend Data Adequately Report Progress? - Knoeppel, Robert Charles; Brewer, Curtis A. (Education Policy Analysis Archives, 2011)
Using Kentucky as a case study, the research described in this paper examines efforts to provide equality of educational opportunity. Standards based educational reform has produced myriad data on student achievement that are used by educators, policy analysts, legislators, and researchers to discern progress. This research makes use of multiple sources of data(CATS index, reading proficiency, math proficiency) in an attempt to more thoroughly consider progress in attempts to ameliorate gaps in student achievement that have been found to exist as related to local wealth. Findings from the study show mixed results. Although local wealth has decreased as a predictor of student achievement in reading, it is still a significant predictor of achievement in math. Gaps are closing more rapidly at the elementary school level which suggests the need to study the process of education at the secondary level. Lastly, student demographics, especially students qualifying for free and reduced lunch continue to be a significant predictor of student achievement. We conclude that changes to state accountability systems that move the unit of analysis from the school to the student level offer the best opportunity to utilize emerging research methodologies that will enable practitioners and analysts to better analyze educational process.